The Nature of Legal Regulations on The Merauke Integrated Food and Energy Plantation Project - Ramadhan, Muhammad Fauzi; Nawi, Syahruddin; Khalid, Hasbuddin; Abbas, Ilham (Journal of Cultural Analysis and Social Change, 2026)
This research was conducted with the objective to analyze the nature of the regulations governing the Merauke Integrated Food and Energy Plantation Project. This research uses a normative-empirical legal approach. The normative approach is conducted through a review of laws and regulations, regional regulations, and customary law related to the protection and preservation of forest resources. The empirical approach examines its implementation in Merauke Regency through interviews with law enforcement officials, customary leaders, and forestry agencies. The results of this research indicate that the nature of legal regulations for the protection and preservation of forest resources in Merauke Regency reflects the importance of forests as a life-support system and living space for indigenous Papuans, with law functioning as an ecological instrument to safeguard their sustainability. However, the existing regulatory framework still reveals disharmony and overlapping norms, which weaken legal certainty and reduce the effectiveness of forest protection. This suggests the need for normative renewal oriented toward ecological justice, positioning the protection of natural and customary forests as a fundamental boundary for development within the Merauke Integrated Food and Energy Plantation Project.